La costruzione dello Stato moderno - Campos Boralevi, Lea (Strumenti per la didattica e la ricerca, 2018)
The second "Notebook of the Modern History Laboratory" takes up and develops some of the interventions presented in the Seminar on Themes and Problems of Modern History, which has been held for more than fifteen years at the SAGAS Department of the University of Florence. The contributions collected here discuss the construction of the modern state from different points of view, through the slow and complex evolution of central sovereignty over autonomy, the role of the courts, the development of diplomacy and its ceremonial and the history of the idea of freedom. Special attention is paid to the cases of the Electorate of Saxony and of the monarchy of France in the 16th century, the Consigli (recommendations) by Scipione Ammirato, the theme of democracy in the Encyclopédie and that of national plurality for the protection of minorities in the Habsburg Empire.